Robotic-assisted Supermicrosurgery in Plastic Surgery: A Systematic Literature Review - Hannah Brown, BS; Ryleigh A. Brown, MPH; Leticia Lenkiu, BS; Aseela SamSam, DO; Joseph Lopez, MD, MBA, FAAP, FACS; Rajendra Sawh-Martinez, MD, MHS, FACS (Plastic and Reconstructive Surgery, Global Open)
Background:. Robotic microsurgery is rapidly changing the surgical landscape by mitigating conventional hand-surgical limitations such as physiological tremor while promoting increased precision in confined spaces through the provision of high-depth microoptics and motion-scaling. The innovation of specialized “super” microsurgical robotic platforms such as Medical Microinstruments’ Symani and Microsure’s MUSA-2 has further bolstered microsurgical toolkits by enabling high-precision microvascular anastomoses in vessels with a diameter of 0.8 mm of less. Methods:. Our team conducted a systematic literature review of the global uses of robotic-assisted supermicrosurgery in plastic and reconstructive surgery. Using Preferred Reporting Items for Systematic Review and Meta-Analyses 2020 flow guidelines, our search yielded 107 articles, of which 16 were eligible based on our inclusion criteria. Results:. Our results showed that lymphaticovenous anastomoses represent 37% of reported plastic and reconstructive surgery supermicrosurgery robot clinical uses, whereas free flaps and nerve repairs comprised just 14% and 2%, respectively. These procedures were found to correspond with significant but short learning curves. Across studies, mean operating times were found to be up to 1.5 times greater than manual techniques and showed a downward trend in time spent. Our analysis revealed that robotic-assisted techniques decreased rates of microtrauma, with anastomotic patency rates of 99.38%. Conclusions:. Although robotic technology represents a significant financial investment and includes training needs, current literature supports evidence of potential long-term net savings due to reliably high patency rates; decreased in-hospital recovery times; the promise of new, expanded surgical options and capabilities; and enhanced career longevity for surgeons.